(untitled) (One Health & Risk Management, 2024)
Scientific research and innovation are activities accepted and recognized worldwide and have an essential role in the economic development and social progress of a country, representing the main factor in increasing labor productivity, the efficiency of the use of material and energy resources, as well as the competitiveness of the economy long-term. Researchers are constantly striving to explore new frontiers and make groundbreaking discoveries. Platforms dedicated to the use of scientific results in different fields are of indisputable importance. The exchange of information between researchers boosts the growth of scientific performance and contributes to a permanent competition to achieve goals, offering solutions to current challenges. The journal "One Health & Risk Management" is a platform to connect researchers from the three key scientific areas of the "One Health" approach. It is confirmed that human and animal health are interdependent and linked to the ecosystems in which they coexist and constantly evolve. According to data from the World Health Organization, more than 70% of contagious human diseases come from contact with animals as well as from the consumption of animal products contaminated with zoonotic pathogenic germs. There are also a number of chemical and radioactive agents, originating from human activity through pollution and contamination, which influence climate change, and as a result, humans and animals suffer the consequences. Talking about the concept of "One Health" implies the need for researchers from various fields to join efforts to improve global health through communication, coordination and scientific collaboration. In today’s interconnected world, people and goods travel long distances, and policies implemented in one region can have a major impact on another. In this context, solving the existing problems requires the increased involvement of scientific research and the strengthening of collaboration between the organizations responsible for these fields: the World Health Organization, the United Nations Food and Agriculture Organization and the World Organization for Animal Health. In this context, the scientific journal "One Health & Risk Management" comes with a major contribution to the consolidation of new scientific research areas and themes with reference to human and animal health, as well as environmental protection.